Assessment moderation in an Australian context: processes, practices, and challenges. Issue 1 (2nd January 2017) - Beutel, Denise; Adie, Lenore; Lloyd, Margaret
ABSTRACT: Moderation is a quality assurance process that plays a central role in the teaching, learning, and assessment cycle in higher education. While there is a growing body of research globally on teaching, learning, and, to a lesser degree, assessment in higher education, the process of moderation of assessment has received even less attention. In a context of heightened accountability and greater transparency in the tertiary sector, the formalising of moderation processes has not been a part of established practice. In light of these changes, the purpose of this qualitative study was to identify and investigate current marking and moderation processes and practices operating within one faculty in a large urban university in eastern Australia to gain insight into the challenges to effective moderation. The findings suggest the need for moderation to be considered holistically as an inherent part of teaching and learning, and the need for ongoing staff development.